The Correlation Of Working Climate And Blood Pressure On The Volunteer Of Traffic Control (Supeltas) In Surakarta - Larasati, Ulima Fadhilah; Darnoto, Sri (Universitas Muhammadiyah Surakarta, 2017)
Each workplace has a hazard factor that may affect the health of the workforce or may result in the onset of occupational diseases. Heat pressure is part of the physical stress that greatly affects workers' activity. Working climate or heat pressure can result in additional burden in blood circulation. The purpose of this research is to analyze the correlation between work climate and blood pressure at Volunteer of traffic control (Supeltas) in Surakarta in 2017. This type of research is non-experimental quantitative using survey analytic method with cross sectional design. The population in this study were members of Supeltas in Surakata as many as 49 people, with a minimum sample size of 43 people. Data sampling was conducted by using total sampling. From the results of the study, it was obtained that the lowest ISBB 29.24oC and the highest is 32.23oC and the result of blood pressure measurement at Supeltas Surakarta in the workplace that exceeds NAB hot work climate as much as 38 people (100%) experienced hypertension, while Supeltas who work in the workplace under the NAB who experienced hypertension as many as 7 people (63.6%) and who did not experience hypertension as many as 4 people (36.4%). The result of statistical test using fisher exact showed that there was a correlation between hot work climate with blood pressure (p = 0,002) on Surakarta traffic regulator volunteer in 2017.